Ligand-Bound Forced Degradation as a Strategy to Generate Functionally Relevant Analytical Challenge Materials for Assessment of CQAs - Giddens, John P.; Schiel, John E. (Frontiers in Molecular Biosciences, 2022)
Therapeutic monoclonal antibodies (mAbs) contain a variety of amino acids that are susceptible to enzymatic, chemical, and physical modifications. These modifications can happen throughout production, purification, formulation, and storage and many are known to affect the biological activity of a mAb. Methods that are able to characterize and evaluate these attributes are critical in order to understand how they might alter biological activity. Methods capable of site-specific monitoring of these critical quality attributes are extremely valuable to biopharmaceutical research but also require well-defined materials with site-specific attribute modifications. Here, we describe the development and application of a strategy to generate functionally relevant analytical challenge materials that have unique site-specific attributes. This method involves the use of a ligand that is bound to the mAb during oxidative stress resulting in unique oxidation patterns with some methionine residues protected while others are exposed to oxidation. These unique materials were used to develop a rapid surface plasmon resonance (SPR) assay that could rapidly detect methionine oxidation in both the Fab and Fc regions using specific molecular probes. The addition of uniquely oxidized materials to our data set enabled us to determine specific methionine residues vital to binding. Further analysis showed that antibody oxidation could also be rapidly detected in multiple domains from qualitative thermal melting using intrinsic tryptophan fluorescence. Methionine oxidation of an antibody was explored in this study, but we envision this method could be useful to explore structure function relationships of a variety of antibody modifications and modifications to other biologically relevant protein drugs.